Identifikasi dan Pola Infestasi Caplak pada Biawak Air (Varanus salvator, Byers, d. 2000) - Kartika Aditiya Amelia; Rahaju Ernawati; Poedji Hastutiek; Boedi Setiawan; Agus Sunarso (Journal of Parasite Science (JoPS), 2020)
The aim of this study is to identify the type of ticks infestation pattern on water monitor lizard (Varanus salvator, Byers, D. 2000) with regard parameters water monitor lizard species, stadium and region of the water monitor lizard’s body. The total samples of 250 ticks from 30 water monitor lizard (18 male lizards and 12 female lizards) were collected every day starting from noon to evening during July to August 2019 at the monitor slaughtering place in Buduran District, Sidoarjo Regency. The tick samples were identified by the permanent mounting slide method without staining and put in bottles containing 10% KOH for 1-10 hours, then each stadium used a nikon eclipse E100 microscope with a 40x magnification binocular microscope. Data was analyzed using Multiple Correspondance Analytics. The result indicate that 30 V. salvator (100%) are positive infested by tick and the samples obtained consisted of 133 Aponomma sp. and 117 Amblyomma sp. in all regions of the body.